The Use of Politeness Strategies in “Gung Ho” Movie (1986) - Yessyca Pratychia (Kata Kita: Journal of Language, Literature, and Teaching, 2017)
This study deals with the politeness strategies used in Gung Ho movie between Hunt and Kazihiro by focusing on the Scollon & Scollon (2001) theory. This research is aimed to find out the types of strategies have been used by Hunt to Kazihiro, Kazihiro to Hunt, and the types politeness strategies mostly used by Hunt and Kazihiro. This research uses descriptive quantitative method. After analyzing the data using Scollon & Scollon theory (2001), there are 34 strategies (25 involvement and 9 independence strategies) have been found in the data analysis. In terms of involvement strategies, both characters made “notice to the hearer’s (interests, wants, needs, and goods)” strategy the most. It is possible because both of them try to build a good relationship by paying attention or notice to each other’s condition since they are from different culture (American and Japanese).